STUDENT PARTICIPATION IN LEARNING SPEAKING SKILLS WITH THE THINK PAIR SHARE MODEL - Rahmah Fadhilah Agustina; Muassomah Muassomah; Nuril Mufidah (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The factor that encourages students to learn a foreign language is to be able to communicate with speakers of the language they learn, including oral communication, because successful language learning requires active student participation to practice the language in context. Participation is essential in the learning process because, fundamentally, learning involves activities that change behavior. Therefore, students must actively engage in the learning process. The purpose of this study is to analyze and describe student participation in learning speaking skills using the think pair share model. This research uses a qualitative design of case study type. The subject of this research in PKPBA UIN Malang, Faculty of Medicine and Health Sciences, pharmacy study program class A. The data collection techniques used are observation and interviews. Based on the results of the research analysis, it can be concluded that the Think Pair Share learning model can create a learning environment that encourages student participation and involvement including giving opinions, providing responses, working on tasks, concluding, and presenting. This will help students reach their full potential, gain better understanding, develop relevant skills, and prepare themselves to face challenges in the real world.